Design and Implementation of FPGA-based Hardware Accelerator for Bayesian Confidence Propagation Neural Network - Wang, Deyu (My University, 2023)
The Bayesian confidence propagation neural network (BCPNN) has been widely used for neural computation and machine learning domains. However, the current implementations of BCPNN are not computationally efficient enough, especially in the update of synaptic state variables. This thesis proposes a hardware accelerator for the training and inference process of BCPNN. In the hardware design, several techniques are employed, including a hybrid update mechanism, customized LUT-based design for exponential operations, and optimized design that maximizes parallelism. The proposed hardware accelerator is implemented on an FPGA device. The results show that the computing speed of the accelerator can improve the CPU counterpart by two orders of magnitude. In addition, the computational modules of the accelerator can be reused to reduce hardware overheads while achieving comparable computing performance. The accelerator's potential to facilitate the efficient implementation for large-scale BCPNN neural networks opens up the possibility to realize higher-level cognitive phenomena, such as associative memory and working memory.
Keywords: Bayesian Confidence Propagation Neural Network (BCPNN), FPGA, Training, Inference